Sustainable Solutions in the Transition to Green Energy: Economic and Environmental Perspectives - Garashov, Vagif (My University, 2026)
Transitioning to green energy - becomes important every year. The world and humanity are developing fast. More emissions releasing to atmosphere and harming the environment. And conventional energy sources will end one day. That’s why countries aim to integrate into renewable energy sources sooner. This research studies the sustainable steps for integration to clean energy. In addition, regions need strong transmission lines to move clean energy. So, thesis also focuses on HVDC. Azerbaijan’s location between Europe and Asia is very strategic. The new interconnection model was proposed and simulated. The new Central Asia → Azerbaijan → Türkiye → Europe interconnection between regions. The 2030 situation model was simulated for four regions. A 5 GW HVDC line was tested and estimated losses using typical HVDC values were calculated. The results of this model show that Central Asia has extra renewable power. Which can be transferred through South Caucasus by corridor to Europe. Also results show the HVDC losses are very low. And Corridor technically worked at full capacity with benefits. To sum up, the new interconnection model shows that the idea is technically possible. This corridor can support clean energy goals in the region. Additionally, corridor can be expanded in future. And this study is useful base for more detailed studies.
Keywords: Azerbaijan -- Electric power systems.; Electric power systems -- Planning.; Electric power transmission.; Green technology.; Renewable energy sources.